RANCANG BANGUN SISTEM INFORMASI MONITORING PEMINJAMAN ALAT LABORATORIUM AKADEMI KEBIDANAN BINA HUSADA SERANG BERBASIS WEBSITE - Raden Kania; Waliadi Gunawan; Abdul Ghofur; Ramdani Budiman; Tauffik Qurohman (Journal of Innovation And Future Technology, 2025)
The laboratory in higher education institutions is one of the facilities that must be available, usually used for practical and trial purposes. At the Bina Husada Banten Midwifery Academy, lecturers and students use the laboratory according to the schedule of certain courses. However, due to limited human resources and the large number of tools used, borrowed tools are often not returned on time, and the recording is still conventional through borrowing and returning books, so it cannot be controlled properly. Therefore, the author tries to design an information system that can monitor the borrowing and returning of laboratory equipment so that it is used and returned according to schedule. Observations, interviews, and literature studies were conducted to collect the necessary data. At the same time, system development was done using the waterfall model and modeling using unified modeling language (UML), PHP programming language, and MySQL database. Through this system design, the borrowing of laboratory equipment can be monitored properly so that the use of equipment can be regulated properly and accurately. The limitation of using a website-based system is that when the internet resource is disconnected or there is no electricity, transactions cannot be carried out, therefore it is necessary to develop a system that can be implemented online or offline.